The use of small‐molecule structures to complement protein–ligand crystal structures in drug discovery. Issue 3 (1st March 2017) - Groom, Colin R.; Cole, Jason C.
Abstract : Small‐molecule crystal structures are of tremendous value in understanding protein–ligand complexes, both individually and as a collection. Abstract : Many ligand‐discovery stories tell of the use of structures of protein–ligand complexes, but the contribution of structural chemistry is such a core part of finding and improving ligands that it is often overlooked. More than 800 000 crystal structures are available to the community through the Cambridge Structural Database (CSD). Individually, these structures can be of tremendous value and the collection of crystal structures is even more helpful. This article provides examples of how small‐molecule crystal structures have been used to complement those of protein–ligand complexes to address challenges ranging from affinity, selectivity and bioavailability though to solubility.